Influence of solvents on polyphenol content and antioxidant activity of fig leaf extracts obtained by maceration and ultrasonic extraction - Merzic, Sabina; Sehanovic, Ajla; Music, Amila; Saric, Asim; Alic, Mehmed; Avdic, Ajla; Huskic, Almina; Yazici, Basaryusuf; Basic, Maida; Pavic, Ivana; Horozic, Emir (International Journal of Advanced Chemistry, 2021)
In this paper, the polyphenol content and antioxidant activity of fig leaf extracts were analyzed. Extraction was performed with methanol, ethanol, acetone and their aqueous mixtures (50:50 v/v). Extractions were performed with stirring at 300 rpm on a vibromix and ultrasonic bath for 15 minutes. The polyphenol content was determined spectrophotometrically using the Folin-Ciocalteu test. Antioxidant capacity was tested using the FRAP and DPPH methods. The results showed a significant effect of extraction of bioactive components using an organic solvent:water mixture in relation to the organic solvent itself. Ultrasonic extraction proved to be a more efficient technique compared to mixing at 300 rpm.Â Â
Keywords: Fig Leaf; Polyphenols; FRAP; DPPH Inhibition.